Understanding Students’ Conceptual Learning in Digital Environments: The Role of Learning Styles and E-Learning Utilization - Alim Ikmal Jamal (ASHA Publishing, 2026)
The advancement of information technology has encouraged transformations in educational systems, particularly through the implementation of e-learning as a digital learning medium. The effectiveness of e-learning is influenced not only by technological availability but also by students’ characteristics, including learning styles. This study aims to examine the effect of learning styles and e-learning utilization on the conceptual understanding of eleventh-grade students at SMKN 8 Makassar. A quantitative correlational approach was employed in this study. The population consisted of 31 students, with 29 students selected as samples using the Slovin formula. Data were collected through Likert-scale questionnaires that had passed validity and reliability testing. Data analysis included descriptive statistics, validity tests, reliability tests, normality tests, linearity tests, multicollinearity tests, Pearson correlation, and multiple linear regression. The findings indicate that all research instruments were valid and reliable. Correlation analysis revealed that learning styles had a positive relationship with conceptual understanding (r = 0.605), while e-learning utilization had a positive relationship with conceptual understanding (r = 0.622). Multiple linear regression analysis demonstrated that learning styles and e-learning utilization simultaneously had a significant effect on conceptual understanding, with an R value of 0.693 and a coefficient of determination of 0.481. These findings indicate that 48.1% of the variation in conceptual understanding can be explained by learning styles and e-learning utilization, while the remaining percentage is influenced by other factors outside the research model. The study highlights the importance of aligning instructional strategies with students’ learning characteristics and optimizing e-learning implementation to improve conceptual understanding.